2021
DOI: 10.3390/cancers13040868
|View full text |Cite
|
Sign up to set email alerts
|

Complete Removal of the Lesion as a Guidance in the Management of Patients with Breast Ductal Carcinoma In Situ

Abstract: Background: Considering highly selected patients with ductal carcinoma in situ (DCIS), active surveillance is a valid alternative to surgery. Our study aimed to show the reliability of post-biopsy complete lesion removal, documented by mammogram, as additional criterion to select these patients. Methods: A total of 2173 vacuum-assisted breast biopsies (VABBs) documented as DCIS were reviewed. Surgery was performed in all cases. We retrospectively collected the reports of post-VABB complete lesion removal and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In our study, we found a statistically significant reduction of the upgrade rate considering the following parameters: age of the patients, lesion size, BIRADs and the complete macroscopical removal of the lesion by VABB, as already documented for the upgrading rate of DCIS to IC [ 39 ]. Moreover, the upgrade rate to IC is significantly reduced when ADH is found only in specimens showing microcalcifications.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, we found a statistically significant reduction of the upgrade rate considering the following parameters: age of the patients, lesion size, BIRADs and the complete macroscopical removal of the lesion by VABB, as already documented for the upgrading rate of DCIS to IC [ 39 ]. Moreover, the upgrade rate to IC is significantly reduced when ADH is found only in specimens showing microcalcifications.…”
Section: Discussionsupporting
confidence: 82%
“…All upstaged cases were good-prognosis invasive carcinomas: all were node negative and HER2 negative. Furthermore, a proportion of women with DCIS will have complete removal of the lesion at biopsy, and subsequently experience a low upgrade rate (8.2%) [31]. A study in the Netherlands addressed the issue of the reliability of preoperative biopsy, and identified several factors that can aid in further risk stratification of women being considered for non-operative management [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasound and mammogram indicated a high complete excision rate, residual tumors were con rmed in 77.5% of cases under the guidance of histologically golden standards. In other studies regarding malignant tumors, complete excision rates were around 33-86% [14,[20][21][22][23][24] . Although the imaging-complete excision of malignant lesions may be achieved, the VABB procedure is not able to entirely replace surgery for breast cancer [18,19,25] .…”
Section: Discussionmentioning
confidence: 83%